Optimization of the steel-fiber dosage in shotcrete used in the Kankberg mine - Larsson, Pontus (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2018)
The Swedish metal company Boliden has since the early 20th century been mining deposits in the mining field commonly referred to as the Skelleftefield in northern Sweden. The youngest of the active mines is the Kankberg mine which is an underground mine whose reserve contains gold and tellurium. The reserve of the mine is split-up into multiple smaller orebodies that are all being mined continuously using a cut- and fill mining method in combination with pillars utilized to ensure stability in certain stopes. The Kankberg mine is unique in the sense that it is situated in very hard rock. That in combination with medium stresses as results of the mining depth results in favorable conditions in terms of needed rock support. Boliden therefore wants to reduce the amount of support material used, without compromising the stability of the support system and the security of the underground personnel. The goal of this thesis is to present a recommend steel fiber dosage to be used in the shotcrete. The recommendation is based upon: Test results of round determinate panel (RPD) tests according to the ASTM C1550-12a (American Society for Testing) standard. Reviews of earlier shotcrete tests conducted by Boliden. A literature study focused on fiber dosages in other underground projects. Stress analyses using numerical methods. Rock inspections and rock classifications. International guidelines regarding fiber dosages used in shotcrete. The results presented within this thesis suggest that the fiber dosage in the shotcrete recipe can be lowered, in favor of cost optimization. The optimal dosage, when factoring in the issues related to the continuous mining, the energy absorption capacity of the shotcrete and general recommendations from studied literature was determined being a dosage of 22.6 kg/m3. The thesis further suggests that large scale tests should be conducted on a full scale before the lowered dosage is adopted in practice.